Irreversible Electroporation - Rubinsky, Boris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This is an brief introduction to the emerging field of irreversible electroporation in medicine. Certain electrical fields when applied across a cell can have as a sole effect the permeabilization of the cell membrane, presumable through the formation of nanoscale defects in the cell membrane. Sometimes this process leads to cell death, primarily when the electrical fields cause permanent permeabilization of the membrane and the consequent loss of cell homeostasis, in a process known as irreversible electroporation. This is an unusual mode of cell death that is not fully understood yet. While the phenomenon of irreversible electroporation may have been known for centuries it has become only recently rigorously considered in medicine for various applications of tissue ablation. A brief historical perspective of irreversible electroporation is presentedfollowed by general reviews on the theory and experiment fundamentals and by reports on the most recent theoretical, experimental and clinical studies.
Historical Review of Irreversible Electroporation in Medicine -- Tissue Electroporation as a Bioelectric Phenomenon: Basic Concepts -- Experimental Studies on Irreversible Electroporation of Cells -- Mechanism of Irreversible Electroporation in Cells: Insight from the Models -- Thermal Aspects of Irreversible Electroporation -- Experimental Studies on Non-thermal Irreversible Electroporation in Tissue -- Finite Element Modeling of in Vivo Electroporation -- Optimization and Numerical Modeling in Irreversible Electroporation Treatment Planning -- The Place of the Electroporation-Based Antitumor Therapies in the Electrical Armamentarium against Cancer -- Irreversible Electroporation: First Patient Experience Focal Therapy of Prostate Cancer -- Human Experience with Irreversible Electroporation -- Irreversible Electroporation Systems for Clinical Use -- The Use of Irreversible Electroporation in Food Preservation.
Keywords: Engineering; Oncology; Cell biology; Electrophoresis; Biomathematics; Microwaves; Optical engineering; Biomedical engineering; Engineering; Biomedical Engineering; Oncology; Cell Biology; Electrophoresis; Physiological, Cellular and Medical Topics; Microwaves, RF and Optical Engineering; Electronic books